Loss prevention and safety promotion in the process industries : proceedings of the 10th International Symposium, 19-21 June 2001, Stockholm, Sweden - Pasman, H. J. (EFCE event, 2001)
This book contains the Proceedings of the 10th International Syposium on Loss Prevention and Safety Promotion in the process industries. The main topics of the conference include; optimisation of operations within the framework of safety, health and environment; safety, health, environment management and performance indicators; risk management experience; safety, health and environment in design and modification of processes and plants; hazardous substance/materials properties; storage and transport of dangerous goods by road, rail, water and pipeline; the prevention, protection and mitigation, and modelling of accidental releases; topics of safety and environment in specific process industries; the impact of legislation and industry initiatives; development of methodology, e.g. of risk assessment.